Serum Exosomal MicroRNAs Predict Acute Respiratory Distress Syndrome Events in Patients with Severe Community-Acquired Pneumonia. (5th August 2019) - Wu, Xu; Wu, Chengzhi; Gu, Wenyu; Ji, Haiying; Zhu, Lei
Abstract : Background . Severe community-acquired pneumonia (SCAP) requiring intensive care unit (ICU) treatment commonly causes acute respiratory distress syndrome (ARDS) with high mortality. This study was aimed at evaluating whether microRNAs (miRNAs) in circulating exosomes have the predictive values for patients at risk of developing ARDS due to SCAP. Methods . ARDS/ALI-relevant miRNAs were obtained by literature search. Exosomes in serum were isolated by ultracentrifugation method and identified by Transmission Electron Microscopy. Then the miR profiling in the exosomes using real-time PCR was analyzed in SCAP patients with or without ARDS. Moreover, multivariate Cox proportional regression analysis was performed to estimate the odds ratio of miRNA for the occurrence of ARDS and prognosis. The receiver operating characteristics (ROC) curves were calculated to discriminate ARDS cases. Finally, the Kaplan-Meier curve using log-rank method was performed to test the equality for survival distributions with different miRNA classifiers. Results . A total of 53 SCAP patients were finally recruited. Ten miRNAs were picked out. Further, a subset of exosomal miRNAs, including the miR-146a, miR-27a, miR-126, and miR-155 in ARDS group exhibited significantly elevated levels than those in non-ARDS group. The combined expression of miR-126, miR-27a, miR-146a, and miR-155 predicted ARDS with an area under the curve of 0.909 (95 % CI 0.815 –1). Only miR-126 was selected to have potential to predict the 28-day mortality (OR=1.002, P=0.024) with its median value classifier. Conclusions . The altered levels of circulating exosomal microRNAs may be useful biologic confirmation of ARDS in patients with SCAP.